Análisis del porcentaje de humedad, materia orgánica y porosidad del suelo de dos tipos de bofedales - Baldoceda, Ángela (2022)
Wetlands are important ecosystems found in the high Andean regions. Climate change and anthropic and anthropogenic activities have caused accelerated losses of this ecosystem. Through the opening of infiltration channels, the formation of artificial wetlands or the increase in the area of ​​natural wetlands has been promoted. This research analyzes the percentage of moisture, organic matter and soil porosity of two wetlands, one managed or artificial and other natural. The samples were collected in the acrotelm at different depths. According to the analysis, the natural wetland, Huachipampa, presents a porosity ranging from low to excellent, while the managed wetland, Tambo Real, presented a porosity ranging from very low to excessive. In relation to the analysis of organic matter, the soil of the Huachipampa wetland has a higher content of organic matter than the Tambo Real wetland. The behavior of soil moisture for each wetland was different, so we have that in Huachipampa the highest moisture values ​​were observed in the middle area of ​​the wetland where the Distichia muscoides mattresses dominate. At Tambo Real, humidity was evaluated based on the influence of the infiltration channel, where three zones were defined: the zone near the canal, the middle zone of the wetland and the zone near the river. The data showed that the highest humidity values ​​were located in the area near the river.